Role of two particle types in bovine rotavirus morphogenesis. - Clark, S M (1980)
The involvement of light (L) and dense (D) bovine rotavirus particle types during virus replication has been studied. It was found that infectious parental L virions are uncoated in vivo to a particle similar to native D particles. Differences in the rate of synthesis and relative yields of L and D particles in MDBK and MA-104 cells have been detected. Results from pulse-chase labeling experiments indicate that D particles serve as morphogenic precursors to the complete L virion.